The book of the British Library - Leapman, Michael (London : British Library, 2012)
As well as holding some of the world's most prized cultural treasures, the British Library is the repository of the nation's collective memory. In this highly illustrated book Michael Leapman tells the Library's story, highlighting the most significant and beautiful items in its care, as well as some of the lesser known
boek